2009
DOI: 10.1007/s00464-009-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Partial amniotic carbon dioxide insufflation (PACI) during minimally invasive fetoscopic surgery: early clinical experience in humans

Abstract: PACI greatly improves fetal visualization during fetoscopic interventions when fetoscopy within fluid meets with difficulties. Continued assessment of its benefits, risks, and safety margins at specialist centers is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 9 publications
4
54
0
Order By: Relevance
“…These groups later abandoned their FSBAR program and transitioned to OSBAR because of a combination of technical failures, complications and fetal death. Two case reports and 1 case series (n = 2, 3 and 16, respectively) from Kohl et al [19,20,21] were excluded because the data were incomplete and reported in a later article (n = 19) [22]. One case report from Pedreira et al [36] was also excluded since all cases have been included in a later more complete study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These groups later abandoned their FSBAR program and transitioned to OSBAR because of a combination of technical failures, complications and fetal death. Two case reports and 1 case series (n = 2, 3 and 16, respectively) from Kohl et al [19,20,21] were excluded because the data were incomplete and reported in a later article (n = 19) [22]. One case report from Pedreira et al [36] was also excluded since all cases have been included in a later more complete study.…”
Section: Resultsmentioning
confidence: 99%
“…The closure technique in the hands of Kohl's group evolved over time. In the early experience (≤30 cases), closure consisted of a double layer of patches (Durasis® fascia patch covered by a Gore® Preclude® Pericardial Membrane skin patch) or a single layer of Gore® Preclude® skin patch [20,21,22]. In the later experience on 51 FSBAR procedures, except for one incomplete closure, repair consisted of either a single layer of Surgisis® skin patch (n = 30/50, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients reported on by Danzer et al [30], Friszer et al [31], Moldenhauer et al [32], Zamłyński et al [33], Bennett et al [34], and Hisaba et al [35] underwent open fetal repair of MMC. For each of the 11 studies, the data The patients reported on by Degenhart et al [28] overlap with those reported on by Kohl [12] in 2014, and the patients reported on by Verbeek et al [29] overlap with those reported on by Kohl et al [11] in 2010. The preliminary findings reported by Pedreira et al [13] in 2014 are also reported in 2016 [27], after completion of the study.…”
Section: Study Characteristicsmentioning
confidence: 44%
“…Proponents of fetoscopic MMC repair argue that this minimally invasive approach reduces the rate of obstetrical complications associated with open fetal MMC repair [10][11][12][13]. However, critics have argued that the high rates of membrane rupture and premature birth -combined with the inability to reliably perform a watertight closure of the MMC defect, thus necessitating postnatal revision of the repair -challenge the notion that fetoscopic MMC repair is associated with less morbidity than open fetal repair [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%